Percutaneous biopsy of retroperitoneal lesions - 10 year experience of a single centre - Dvorak, Petr; Hoffmann, Petr; Balik, Michal; Hoffmannova, Martina; Kopecky, Jindrich; Dvorakova, Radka; Nova, Marketa (Biomedical papers, 2020)
Aims: To retrospectively evaluate the technical features, efficacy, accuracy, appropriate complications, and relationships among monitored parameters of computed tomography-guided biopsies of the retroperitoneum-located processes. Methods: From December 2008 to December 2018, 208 percutaneous biopsy procedures for tumors, sized 14 - 190 mm in diameter (median size 57.5 mm), were performed on patients with suspected retroperitoneal tumorous process on imaging examinations. The patients were men in 124 cases and women in 84 cases, aged 20 to 90 years (median age 63.2 years). Skin to lesion distance was variable; from 43 cm to 178 cm (median length 108.5 cm). Results: In 202 cases (97.1%) results were true positive or true negative; only 6 interventions (2.9%) were histologically false negative and had to be confirmed surgically. DLBCL and metastatic disease to the retroperitoneal lymphatic nodes were the most common diagnoses (23.1% each); lymphoma types were verified in 40.9% of cases. 7 complications in total were revealed, 6 of which were minor hemorrhages, and in one case ureteral injury was detected. A statistically significant relationship between the hypervascular process and complication incidence (P=0.00166) and needle gauge (P=0.01427) was identified. Conclusion: Percutaneous CT-guided biopsy performed in patients with a suspected retroperitoneal tumorous process had a high accuracy in establishing the correct diagnosis including histological subtyping. Simultaneously, the complication rate was low.
Keywords: core needle biopsy; retroperitoneal process; percutaneous approach; complications; hypervascular mass.